The politics of legal empowerment: Legal mobilisation strategies and implications for development - and Domingo, Pilar; O'Neil, Tam (ODI, 2014)
? Legal mobilisation can improve the lives of poor or marginalised people by: o contributing to pro-poor change in policy, law and regulation of service delivery across different sectors; o advancing the realisation of rights, and achieving redress for rights violations; o contesting unjust and illegal practices of resource allocation and power relations, including in relation to land and natural resources; o enabling citizens to exercise social accountability through legal action. ? The outcomes of legal empowerment of the poor are not politically neutral and need to be understood within broader social and political environments; ? Better coordination between justice, sector and governance interventions will maximise the development and social impact of international support for legal empowerment.